Internacionalização da pós-graduação Stricto Sensu no Brasil: um estudo da mobilidade estudantil no período de 2003 a 2016 - Nogueira, Fabiana Araújo (2020)
This dissertation aims to analyze the policies and guidelines for the internationalization of the Brazilian stricto sensu postgraduate course from 2003 to 2016, taking as a reference the student mobility promoted by the Coordination for the Improvement of Higher Education Personnel and the National Development Council Scientific and Technological. It is considered that internationalization is not a new phenomenon, however, nowadays it takes on a new configuration in view of the globalization process and the development of technologies and communication. Brazil, due to its position in the educational rankings, is inserted in the internationalization process in a peripheral way, although at present, several initiatives have been implemented to consolidate this process. The main guiding documents for internationalization policies for higher education are the policy documents prepared by the Ministry of Science and Technology, whose guidelines are contemplated in the National Postgraduate Plans and have served to induce the main actions of the agencies that promote national research. The research approach adopted was historical dialectical materialism. The technical-methodological procedures used to carry out the research were bibliographic and documentary. Historical series were also prepared based on Capes' georeferential platform (Geocapes) in order to show the evolution of student mobility data at the international level provided by funding from Capes and CNPq. The research data show that there is a close articulation between the planning documents prepared by the Ministry of Science and Technology, the National Postgraduate Plans and the induction of the Capes and CNPq development policy. This movement is much greater in the years between 2003 and 2015, when a conception of a developmental state and of encouraging the internationalization of education at both the undergraduate and graduate levels is in force in the country. It is considered that this was a period of great investment for the internationalization of Brazilian postgraduate courses, in which there was a greater expansion in the number of scholarships awarded. Despite the significant increase, it is emphasized that greater investment in the distribution of these scholarships is necessary to contribute to increase the production of knowledge and the development of technology and to strengthen the country's technical and scientific base.